Die Kiefernblattwespen Weißrusslands und ihre Parasiten (Hymenoptera: Diprionidae). - Rywkin, Boris W. (Contributions to Entomology = Beiträge zur Entomologie, 1957)
Five outbreaks of Neodiprion sertifer Geoffr. and one of Diprion pini L. in the pine groves of the Bjelo Russian SSR happened between 1928 and 1951. Their population ecology, especially their parasites, were studied during this time. 21 species of parasites were found, 3 of them attacking the eggs, 12 the larvae, and 6 the cocoons. The principles of biology (flight-time, number of generations, sex-rate, etc.) of the parasites are discussed. The composition of parasites was found to change locally and temporally. The most constant and widely distributed parasite was the chalcid fly Dahlbominus fuscipennis Zett. (cocoon parasite). The outbreaks of N. sertifer and D. pini were induced by meteorological conditions, while episites, parasites, and diseases were found to be the causes of the break-down.